Anthropology of the Finno-Ugric Peoples: The Question of Pigmentation in the Aspect of Application - Murat A. Dzhaubermezov1; Natalia V. Ekomasova; Ongar S. Chagarov; Ekaterina A. Tokareva; Liliya R. Gabidullina; Zemfira R. Sufyanova; Irina M. Khidiyatova; Elza K. Khusnutdinova (Oriental Studies)
Introduction. The geographical feature of the Volga-Ural region is its location on the border of Europe and Asia, which, together with the proximity to the Caspian steppes, Ciscaucasia and Siberia, facilitated as the formation of many migration and trade routes connecting these regions in different historical periods, which in turn affected the ethnogenesis of the peoples of the region. Genetic features underlying the inheritance of human pigmentation features are the subject of active study by molecular and population geneticists. Goals. The work aims to study the distribution of alleles and genotypes of polymorphic variants rs12913832 of the HERC2 gene and rs1042602 of the TYR gene in the Mordvin and Udmurt populations. Materials and methods. The investigated material includes DNA isolated from the peripheral blood of Udmurts (N = 95) and Mordvins (N = 59). Blood sampling was performed after signing an informed consent to participate in the scientific study. A comparative analysis was conducted between the studied populations and populations of the world. Results. Our study revealы statistically significant differences (p≤0.05) in the distribution of allele frequencies and genotypes of polymorphic variants of rs12913832 of the HERC2 gene and rs1042602 of the TYR gene in the Mordvin and Udmurt populations. The results of the study are consistent with the data of anthropologists on the analyzed ethnic groups and are an important link in the study of the ethnogenesis of the Finno-Permian populations of Russia. Conclusions. These features of the distribution of allele frequencies of melanogenesis genes in the Mordvins and Udmurts should be taken into account in population genetic, ethnological, as well as in associative and pharmacogenetic studies.